Do multipartite correlations speed up adiabatic quantum computation or quantum annealing? - Batle, J.; Raymond Ooi, C.H.; Farouk, A.; Abutalib, M.; Abdalla, S. (Springer Verlag (Germany), 2016)
Quantum correlations are thought to be the reason why certain quantum algorithms overcome their classical counterparts. Since the nature of this resource is still not fully understood, we shall investigate how multipartite entanglement and non-locality among qubits vary as the quantum computation runs. We shall encounter that quantum measures on the whole system cannot account for their corresponding speedup.